Scleroderma 'en coup de sabre'. - David, J (1991)
A case of scleroderma 'en coup de sabre' presenting with uveitis, predominantly posterior, and intractable grand mal seizures is described. The histopathology specimens and neuroradiology investigations reaffirm the clinical impression that inflammation is not solely confined to the skin in this form of linear scleroderma.